Viscosity Sensitive Dyes for Determining the Rheological Properties of Hydrogels in Biological Tissues - Tatarets, A.L.; Shkand, T.V.; Чиж, М.О.; Sleta, I.V.; Sandomirsky, B.P.; Patsenker, L.D. (The 14 th Conference on Methods and Applications in Fluorescence MAF 14 Würzburg, Germany. 13-16 September 2015. 232., 2015)
Viscosity sensitive dyes for determining the rheological properties of hydrogels in biological tissues
Tatarets A.L., Shkand T.V., Chizh M.O., Sleta I.V., Sandomirsky B.P., Patsenker L.D. Viscosity sensitive dyes for determining the rheological properties of hydrogels in biological tissues. The 14 th Conference on Methods and Applications in Fluorescence MAF 14 Würzburg, Germany. 13-16 September 2015. 232.
Keywords: hydrogel; biological tissue